# Find dydx, if x = em, y = em Solution: Given, x = em and y = em Now, y = em Diff.w.r.to m, dydm=emd□dm ∴ dydm=em⋅12m .....(i) Now, x = em Diff.w.r.to m, dxdm=□ .....(ii) Now, dydx=dydx□ ∴ dydx=em□em - Mathematics and Statistics

Fill in the Blanks
Sum

Find ("d"y)/("d"x), if x = em, y = "e"^(sqrt("m"))

Solution: Given, x = em and y = "e"^(sqrt("m"))

Now, y = "e"^(sqrt("m"))

Diff.w.r.to m,

("d"y)/"dm" = "e"^(sqrt("m"))("d"square)/"dm"

∴ ("d"y)/"dm" = "e"^(sqrt("m"))*1/(2sqrt("m"))    .....(i)

Now, x = em

Diff.w.r.to m,

("d"x)/"dm" = square    .....(ii)

Now, ("d"y)/("d"x) = (("d"y)/("d"m))/square

∴ ("d"y)/("d"x) = (("e"sqrt("m"))/square)/("e"^"m")

∴  ("d"y)/("d"x) = ("e"^(sqrt("m")))/(2sqrt("m")*"e"^("m")

#### Solution

Given, x = em and y = "e"^(sqrt("m"))

Now, y = "e"^(sqrt("m"))

Diff.w.r.to m,

("d"y)/"dm" = "e"^(sqrt("m"))("d"sqrt("m"))/"dm"

∴ ("d"y)/"dm" = "e"^(sqrt("m"))*1/(2sqrt("m"))    .....(i)

Now, x = em

Diff.w.r.to m,

("d"x)/"dm" = em    .....(ii)

Now, ("d"y)/("d"x) = (("d"y)/("d"m))/(("d"x)/("dm"))

∴ ("d"y)/("d"x) = (("e"sqrt("m"))/(2sqrt("m")))/("e"^"m")

∴  ("d"y)/("d"x) = ("e"^(sqrt("m")))/(2sqrt("m")*"e"^("m")

Concept: Derivatives of Parametric Functions
Is there an error in this question or solution?
Chapter 1.3: Differentiation - Q.6
Share